2011
DOI: 10.1179/174367510x12753884125361
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of interface interactions between thermodynamically stable oxides and Al containing melts

Abstract: Scandia, yttria and erbia are thermodynamically stable oxides and could be used as a structural material for crucibles, in order to avoid contamination of the melt. These oxides have similar wetting behaviour in contact with aluminium containing melts, but different interaction characteristics and different interfacial products. When yttria and erbia substrates are exposed to Al containing melts, the substrate decomposes, large amounts of Y or Er are released into the melt and a thick interaction layer consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is known that at lower temperatures (such as 475°C), the YAM phase becomes unstable and decomposes to a mixture of YAP and yttria [14]. Thus, the fact that YAM has disappeared during heat treatment was not a surprise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that at lower temperatures (such as 475°C), the YAM phase becomes unstable and decomposes to a mixture of YAP and yttria [14]. Thus, the fact that YAM has disappeared during heat treatment was not a surprise.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are different reports regarding the stability of the phases in the Y-Al-O system and it appears that phase stability depends on the composition of the surrounding matrix. In studies of the stability of Y-Al-O phases that focused on the Y 2 O 3 -Al 2 O 3 system, it was concluded that YAG is the most stable phase [13,14]. In a study focusing on a nickel-based austenitic steel (PM6000), Schaffer et al [15] concluded that the YAH is the most stable phase.…”
Section: Discussionmentioning
confidence: 99%